The development of horticulture in Russia: trends, problems, prospects - I. M. Kulikov; I. A. Minakov (Аграрная наука Евро-Северо-Востока)
Particularly acute is a problem of supplying the population of our country with fruit and berry production. Gardening does not satisfy the needs of the population in this product. The ratio of imported products is account for 73%. In the circumstances, it is important to ensure food security, which plays an important role in import substitution. Modern state and tendencies of development of gardening, its placement on the Federal districts, economic efficiency of production of fruits and berries is analysed in the article. There is a tendency of reduction of the area of plantations with a slight increase in the volume of production of fruit and berry goods, decreasing state support, the concentration of gardening in the households. The achieved level of profitability does not provide the expanded reproduction in the industry. It justifies main directions of increasing the production of fruit and berry goods in the regions of industrial and risky horticulture. The solution of this problem will contribute to the concentration of horticulture in specialised enterprises farms; transforming industry on the innovative path of development; increasing productivity of existing orchards and berry fields on the intensification of production; increase the gross harvest of fruit in the result of the establishment of new intensive orchards; the sustainable use of farmed products, reduction of losses at the stages of production, storage, processing, transportation and sales as a result of development of agroindustrial integration; increasing marketability of horticulture in households through the establishment of consumer cooperatives; improvement and increase of the state support of the industry.